Adult acute megakaryoblastic leukemia with persistent diarrhea and extreme thrombocytosis: A very unusual case - Nevin Alayvaz Aslan; Gülsün Gülten (Indian Journal of Pathology and Microbiology)
Acute megakaryoblastic leukemia (AML-M7) is rarely seen in adult patients and patients usually present with cytopenias. Here we discuss diagnostic challenges and pathologic features in a patient with AML-M7 who presented with thrombocytosis and diarrhea. A 63-year-old male patient presented with persistent diarrhea lasting for 2 months, fatigue, and thrombocytosis. The diagnostic workup included a stool analysis, endoscopy colonoscopy, and imaging studies; however, these studies did not reveal any possible etiology. The hematologic evaluation included peripheral blood smear, bone marrow aspiration and biopsy, flow cytometry, and cytogenetic analysis. Eventually, according to pathologic and flow cytometric findings, a diagnosis of AML-M7 was made. Diagnosis of AML-M7 may be challenging, especially in adult patients with atypical presentation. Patients with megakaryoblastic leukemia respond poorly to standard induction regimens and they should be advised to participate in a clinical trial.